Analyzing The Risks P-Hailers Face On The Road - Theenathayalan, Durgeshwar (Universiti Sains Malaysia, 2022)
P-hailing, in general, refers to the delivery of packages and food using an online in-order app like foodpanda, grab, lalamove, shopee, DeliverEat, and many others. In Malaysia, the majority of deliveries are made on motorcycles and are mainly composed of freelancers that ride motorcycles and have flexible schedules. This industry prefers employees to use motorbikes for transportation since they are more convenient and they can get somewhere faster, weave through traffic, and use less petrol and maintenance. It has been widely reported that p-hailing workers have been hurt severely, become permanently disabled, or even passed away in road crashes. Because there is little literature on the work-related road safety of p-hailers, a framework was formulated to identify risk factors within the complex system that influences the safety of riders who receive orders from the Queensbay Mall, Penang area. This is necessary to manage and reduce work-related road accidents cost phailers' lives, well-being, and the nation's economy. The study has identified critical risk features for p-hailers in the study area and has recommended mitigation measures to manage the risks on the road. They include measures that the p-hailers have to improve themselves, the responsibility of the company and vehicle owner, as well as possible policies and regulation for the authority.